Unlocking Clinical Precision Through Polygenic Risk Prediction - Sathian, Brijesh; Iqbal, Javed; Banerjee, Indrajit; Al Hamad, Hanadi (Nepal Journal of Epidemiology, 2024)
Genomic medicine has undergone significant changes over the last decade. The Polygenic Risk Score (PRS), which combines the impact of hundreds to millions of genetic variations to approximate an individual's risk of developing a complex disease (such as coronary artery disease, diabetes, or Alzheimer's disease), is one of the most promising tools. In comparison to monogenic variants, which can carry high and uncommon risks, polygenic models offer predictive capabilities for the population. However, these findings have not yet been translated into clinical care.